EPIDEMIOLOGICAL AND ETIOPATHOGENESIS ASPECTS OF LEPROSY - Desi Oktariana; Fifa Argentina; Kemas Ya’kub Rahadiyanto; Phey Liana; Evi Lusiana; Nia Savitri Tamzil; Gita Dwi Prasasty (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
Leprosy is an infectious disease caused by the acid-fast bacillus, namely Mycobacterium lepra. The entry of Mycobacterium leprae into the body can trigger various immune responses. in some individuals, an adequate immune response can prevent the development of this disease, but in other individuals it can develop into a severe form that can result in disability. Leprosy is widespread throughout the world, especially in tropical/subtropical areas. The highest incidence rates are in India, Brazil and India. Eradicating this disease is still a challenge, especially in endemic areas like Indonesia. Therefore, this article aims to review the basic concepts of leprosy, especially in the epidemiological and etiopathogenesis aspects of leprosy, so that it can be used as a reference for further research.